Novel Aspects Concerning the Functional Cross-Talk between the Insulin/IGF-I System and Estrogen Signaling in Cancer Cells - De Marco, Paola; Cirillo, Francesca; Vivacqua, Adele; Malaguarnera, Roberta; Belfiore, Antonino; Maggiolini, Marcello (Frontiers in Endocrinology, 2015)
The insulin/IGF system plays an important role in cancer progression. Accordingly, elevated levels of circulating insulin have been associated with an increased cancer risk as well as with aggressive and metastatic cancer phenotypes. Numerous studies have documented that estrogens cooperate with the insulin/IGF system in multiple pathophysiological conditions. The biological responses to estrogens are mainly mediated by the estrogen receptors (ER)α and ERβ, which act as transcription factors; however, several studies have recently demonstrated that a member of the G protein-coupled receptors, named GPR30/G-protein estrogen receptor (GPER), is also involved in the estrogen signaling in normal and malignant cells as well as in cancer-associated fibroblasts (CAFs). In this regard, novel mechanisms linking the action of estrogens through GPER with the insulin/IGF system have been recently demonstrated. This review recapitulates the relevant aspects of this functional cross-talk between the insulin/IGF and the estrogenic GPER transduction pathways, which occurs in various cell types and may account for cancer progression.